Linguistics in a Colonial World : a story of language, meaning, and power - ERRINGTON, James Joseph, 1951- (Blackwell Pub, 2008)
"As knowledge of exotic languages became important for colonial power, linguistic scholarship became a crucial contributing element to colonial regimes. Linguistics in a Colonial World draws on both original texts and critical literature to survey the methods, meanings, and uses of linguistics in and for colonial projects over three centuries. By focusing on the shaping effects of linguists' work on identities and communities, this book foregrounds their field's larger meanings and uses for the practical and ideological challenges of colonial rule. Additionally, it traces continuities between colonial and postcolonial politics of culture as they emerge in contemporary controversies over language endangerment and rights in a globalizing 21st century."--BOOK JACKET.